PET Imaging of Steroid Hormone Receptor Expression - Louis Allott; Graham Smith; Eric O. Aboagye; Laurence Carroll (Molecular Imaging)
Steroid hormone receptor (SHR) expression and changes in SHR expression compared to basal levels, whether upregulated, down-regulated, or mutated, form a distinguishing feature of some breast, ovarian, and prostate cancers. These receptors act to induce tumor proliferation. In the imaging context, total expression together with modulation of expression can yield predictive and prognostic information. Currently, biopsy for histologic assessment of SHR expression is routine for breast and prostate cancer; however, the technique is not well suited to the heterogeneous tumor environment and can lead to incorrect receptor expression assignment, which precludes effective treatment. The development of positron emission tomography (PET) radioligands to image receptor expression may overcome the difficulties associated with tumor heterogeneity and facilitate the assessment of metastatic disease.